Surgical site infection among hospitalized patients in palestine: association with in-hospital preoperative time stay, biological and clinical characteristics - Alaeddin Abu-Zant; Hamzeh Al Zabadi; Mariam Hassan; Neven Halabi; Niveen Zaqah; Ibrahim Taha; Mohammad Abuawad (BMC Research Notes)
Abstract Objective This study aimed to assess the correlation between pre-operative hospital stay, patient characteristics, clinical variables, and the occurrence of surgical site infections (SSIs) among patients undergoing major surgeries at An-Najah National University Hospital in Palestine. The data presented stem from a dedicated retrospective cohort review and are not part of a larger research project. Results Out of 200 surgical patients, 7% developed SSIs. Most participants were male (66%), over 50 years old (48%), and underwent elective surgery (88.5%). Significant factors associated with SSIs included smoking, surgical urgency, wound classification, low pre-operative hemoglobin, blood transfusion, type of surgery, hospital stay duration, and use of pre-operative antibiotics. Specifically, smoking was associated with a higher infection risk (p = 0.02), though it only showed borderline significance in multivariate analysis (adjusted odds ratio 5.49; 95% CI 0.96–31.25; p = 0.06). Wound types and other variables did not retain statistical significance after adjustment. These findings suggest the importance of addressing modifiable factors like smoking and optimizing surgical care pathways to reduce infection risk.